Spirulina platensis’s phycocyanobilin as an antiangiogenesis by inhibiting VEGFR2-VEGFA pathway in breast cancer: in silico study - Jayanti, Dewa Ayu Putu Ismartati Sukma; Abimanyu, I Gede Agni Marwan; Azzamudin, Haidar (JSMARTech, 2021)
Breast cancer is a cancer type that leads to many women deaths. The causes are from the primary tumour and other progressions such as metastatic and angiogenesis. Some therapy strategies have been developed to treat breast cancer, but they are not good enough for treating breast cancer progressions. Spirulina platensis has a phycocyanin and a phycocyanobilin, known as antioxidant and antiinflammatory bioactivities. This study identified anticancer activity of phycocyanobilin from Spirulina platensis. We also investigated the phycocyanobilin mechanism in breast cancer inhibition through VEGFR2-VEGFA pathway. In silico analysis was conducted the inhibition modelling of phycocyanobilin to the VEGF-VEGFR pathway. The VEGF and VEGFR proteins were taken out from Protein Data Bank (PDB) database and were prepared with BIOVIA Discovery Studio 2019. Phycocyanobilin as a ligand was obtained from PubChem and prepared with PyRx. The molecular docking was conducted using HEX 8.0.0 CUDA and the last step is the protein-ligand complexes were visualized and analyzed using BIOVIA Discovery Studio 2019. It results in five protein-ligand complexes in which the receptor-ligand complex VEGFR2-[VEGFA-phycocyanobilin] can inhibit the angiogenesis process by phycocyanobilin binds to VEGFA, and it prevents the angiogenesis process by blocks the VEGFR2 and stops VEGFA to bind with VEGFR2. Thus phycocyanobilin has potential as an anticancer agent especially inÂ breast cancer as an antiangiogenesis.